Proposed high gain single DC-source SC-MLI topology for solar PV grid integration applications - Mohammad, Khan; Arif, M. Saad; Md. Ayob, Shahrin; Alrajhi, Hasan; Alam, Mohd Sarfaraz; Ahmad, Mohd Faraz (Institute of Advanced Engineering and Science, 2025)
Multilevel inverters (MLIs) are a key solution for converting DC to AC power. In this article, an improved single-source SC-MLI topology is developed for solar PV applications. It consists of 12 unidirectional switches, 3 capacitors, and 3 diodes to provide sextuple voltage boosting with a lower cost function. Since the capacitor's voltage is self-balanced, there is no need for an additional circuit or sensors, bringing down the circuit's complexity. A simple and fundamental frequency-based control strategy, nearest-level pulse width modulation, is applied to assess the viability of the proposed topology. As a result, the proposed topology has an efficiency of over 97%, and it can generate 13 levels with a total harmonic distortion (THD) of 6.51%. Comparative analysis is performed to show the feasibility of the proposed topology which outperformed other 13-level similar topologies in terms of component count, cost factor, and boosting factor. The proposed topology's performance is evaluated under static and dynamic loads. Furthermore, the thermal analysis is performed using PLECS software to determine the efficiency of the circuit topology. Finally, the feasibility of the proposed circuit is verified for solar PV application.